Genetic diversity analysis of Chaugarkha goat using microsatellite markers - GANIE, Z A; KUMAR, D; KUMAR, SUNDIP; SHAHI, B N; GHOSH, A K (The Indian Journal of Animal Sciences, 2017)
Genetic variability within Chaugarkha breed of goat was studied using microsatellite markers from 25 blood samples of unrelated animals. A set of 15 microsatellite markers were used for PCR and the DNA profiles were scored from the gel that were further analyzed using standard population analysis software. The observed number of alleles varied from 5 to 9 with a mean of 7.20±0.34. The effective number of alleles varied from 2.62 to 6.76 with a mean of 4.82±0.07. The average observed heterozygosity ranged from 0.80 to 0.92 with an average value of 0.83±0.01. The average expected heterozygosity ranged from 0.63 to 0.87 with an average value of 0.79±0.02. The within population Nei’s average expected heterozygosity/gene diversity ranged from 0.24 to 0.85 with an average value of 0.32±0.02. The PIC values ranged from 0.24 to 0.54 with an average of 0.32±0.02. The values of Shannon’s information index were in the range of 1.14 to 2.00 with an average of 1.67±0.07. The level of genetic variability indicated the possibility for further genetic improvement of Chaugarkha goats.